2004
DOI: 10.1038/sj.jea.7500310
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organic pollutants in dusts that settled indoors in lower Manhattan after September 11, 2001

Abstract: The explosion and collapse of the World Trade Center (WTC) was a catastrophic event that produced an aerosol impacting many residents, workers, and commuters after September 11, 2001. In all, 12 bulk samples of the settled dust were collected at indoor locations surrounding the epicenter of the disaster, including one sample from a residence that had been cleansed and was once again occupied. Additionally, one sample was collected from just outside a fifth story window on the sill. These samples were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…In a study of settled outdoor dust collected 4 days after the towers collapsed, more than 98% of the particles had an aerodynamic diameter exceeding 10 µm and a very alkaline pH [14]. Studies of settled dust inside buildings surrounding the WTC showed similar characteristics to those observed outdoors [15,16].…”
Section: Occupational Inhaled Toxicant Exposures At the World Trade Csupporting
confidence: 54%
“…In a study of settled outdoor dust collected 4 days after the towers collapsed, more than 98% of the particles had an aerodynamic diameter exceeding 10 µm and a very alkaline pH [14]. Studies of settled dust inside buildings surrounding the WTC showed similar characteristics to those observed outdoors [15,16].…”
Section: Occupational Inhaled Toxicant Exposures At the World Trade Csupporting
confidence: 54%
“…However, dust and soot from the WTC disaster also deeply penetrated residential and commercial buildings, leaving thick layers of residue (33)(34)(35). Human indoor activities and contaminated central ventilation, heating, and cooling systems can continually resuspend settled dusts into the air; therefore, indoor air may represent a continuing source of exposure to PAHs (and other particle-related pollutants) that should be considered.…”
Section: Resultsmentioning
confidence: 99%
“…It has been estimated that approximately 70% of the towers' structural components were pulverized during the collapse, producing small-(2.5-10 m) and large-(Ͼ10 m) sized respirable particulates (1)(2)(3)(4)(5)(6)(7)(8)(9). Along with the collapse and pulverization of the buildings, structural fires persisted until mid-December, releasing products of combustion/pyrolysis (4,6,10). The necessary use of gasoline-and diesel-powered heavy machinery to remove approximately 1,500 million kilograms of rubble reaerosolized dust and produced additional combustion products (4,8,9).…”
mentioning
confidence: 99%